2004
DOI: 10.1021/ja046900n
|View full text |Cite
|
Sign up to set email alerts
|

Protein Encapsulation in Mesoporous Silicate:  The Effects of Confinement on Protein Stability, Hydration, and Volumetric Properties

Abstract: On the basis of the predictions of statistical-thermodynamic models, it is postulated that excluded volume effects may play a significant role in the stability, interaction, and function of proteins. We studied the effects of confinement on protein un/refolding and stability. Our approach was to encapsulate a model protein, RNase A, in a mesoporous silica, MCM-48, with glasslike wall structure and with well-defined pores to create a crowded microenvironment. To the best of our knowledge, this is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 12 publications
10
148
1
Order By: Relevance
“…For example, Ravindra et al [32] found that, upon being confined within the pores, with sizes averaging ~25 Å, of a silica glass, the melting temperature of ribonuclease A is raised by ~30° C. The measured increase in melting temperature for the 124-residue protein is in quantitative agreement with predicted stabilization by pores of such sizes (see Fig. 2).…”
Section: Experimental Studies In the Test Tube Enhancement Of Foldingsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, Ravindra et al [32] found that, upon being confined within the pores, with sizes averaging ~25 Å, of a silica glass, the melting temperature of ribonuclease A is raised by ~30° C. The measured increase in melting temperature for the 124-residue protein is in quantitative agreement with predicted stabilization by pores of such sizes (see Fig. 2).…”
Section: Experimental Studies In the Test Tube Enhancement Of Foldingsupporting
confidence: 65%
“…Two kinds of encapsulation are now widely used. The first is formed by nanoporous silica gels or glasses [32][33][34][35] or polyacrylamide gels [36]; the second is formed by sodium bis(2-ethylhexyl) sulfosuccinate (AOT) reverse micelles [37][38][39][40][41]. In both cases, the cage sizes can be controlled.…”
Section: Experimental Studies In the Test Tube Enhancement Of Foldingmentioning
confidence: 99%
“…34−36 On the way to the native state, Trp-cage visits a proline-detached (P d ) state lacking a fully formed 3 10 helix, such that Pro12 is detached from the hydrophobic core. 35 Both the I (B 3 ) and P d (B 4 ) states can be identified here in Figure 3, although our states have slightly less helical content than those identified previously.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The folded medoids (5 1 and 5 2 ) have a cosine value of ∼-0.4 because the Trp residue is packed within the hydrophobic core of the protein. In medoid 5 10 , the Trp side chain actually forms a 90°angle with the wall.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10 nm diameter) 52 can be encapsulated into the mesopore network despite the fact that the pore size is similar to that of protein. 73 Interestingly, Hb (pI = 6.8) is still negatively charged when dissolved in phosphate buffer at pH 7.4. Still, the EE% of Hb reached 97%, while for AP-MSNs the EE% was 43% and for AEP-MSNs, 47%.…”
Section: Protein Loading Studiesmentioning
confidence: 99%